Appraising surface water quantity and quality in the Upper Arkansas River Basin in Chaffee County, Colorado - Steed, G. H., author; Gates, T. K., author; Niemann, J. D., author; Labadie, J. W., author; Colorado State University, publisher (Colorado State University. Libraries, 2011)
The Arkansas River, one of four major rivers that begin in Colorado, has the largest drainage basin in the state and serves as a vital source of water. At peak flows, the Arkansas River swells by 70% through Chaffee County, in the heart of the Rockies, and only increases by 20% before exiting the mountains onto the high plains near Pueblo. The production of this discharge depends on a complex natural system of snowmelt and groundwater-stream interactions, as well as on numerous human interventions. The Arkansas valley in Chaffee County, from Granite to Salida, is characterized as an intermountain, high altitude, agricultural, small-municipal, and recreational region. Increasing demands on the stream-aquifer system have necessitated more up-to-date, integrated, and technology-driven data to assist water users, managers, and decision makers in moving toward optimal overall water use. Monthly synoptic measurements and triannual water sampling over July 2009 – January 2011 at 19 river and tributary sites provide data on discharge; dissolved oxygen; pH; specific conductance; oxidation reduction potential; temperature; and major dissolved ions, uranium, selenium, and other select minerals. Data analysis for the range of hydrologic conditions during the study period reveals flow conditions similar to long-term averages. Relationships of specific conductance and total dissolved solids derived from field samples yields equations useful for estimation of mass loading in the river system. Spatial and temporal analysis of tributary to river discharge and dissolved solids loading helps quantify and qualify water sources as well as potential aquifer interactions. Overall water quality is good, with some constituents worthy of continued active monitoring.
Hydrology days 2011
AGU hydrology days 2011
2011 annual AGU hydrology days was held at Colorado State University on March 21 - March 23, 2011.